Contrast between Water‐ and Ethanol‐Based Antioxidant Assays: Aspen (Populus tremula) and Black Poplar (Populus nigra) Extracts as a Case Study. Issue 4 (18th July 2014) - Benedec, Daniela; Oniga, Ilioara; Muresan, Bianca; Mot, Augustin C.; Damian, Grigore; Nistor, Adriana; Silaghi‐Dumitrescu, Radu; Hanganu, Daniela; Duma, Mihaela; Vlase, Laurian
Abstract Water‐based antioxidant assays such as TEAC method, Folin–Ciocalteu assay, the newly developed physiological relevant enzymatic assay HAPX, EPR radicals detection and ethanol based antioxidant assays such as the well‐known DPPH bleaching assay and another EPR method were employed, revealing several aspects of the antioxidant activities of Populus tremula and Populus nigra extracts. A distinct behavior between these two types of assays could be observed in our samples. Alkali‐generated EPR‐detectable free radicals are described here for the first time in Populus sp. extracts. The shape of these signals and the conditions under which they were obtained point to polyphenolic compounds as the sites of the radicals – as confirmed by HPLC‐MS chemical analysis. Besides their antioxidant activity, the antibacterial activity of these extracts reconfirms their biological activity of these widespread herbal medicinal products. Practical Applications Since the antioxidant activity of pharmaceutical and food‐based products is one of the properties that is usually evaluated for their quality, this study aims to draw attention at the variables that might influence the parameters used to estimate this property. As such, this research shows that a set of methods, based on different mechanisms, should be employed rather than only one or two classical methods. In addition, a relatively newly introduced method, based on EPR, detected semiquinone anion radicals is also described, which might be applied for other polyphenol‐rich food‐based products concerning antioxidant activity assessment.